a) x² : x² ; b) 3x² : x ; c) -12x²y : (2x) ; d) x² : x³ ; e) 3x · (-4x) ; f) a² : a² ; g) 2x + 6 + 3x - 8 ; h) (x + 4 ) - ( x + 4 ) ; i) -(4x + 7 ) + ( 4x + 7 ) ; j) (x - 1 ) ( x + 2 ) ; k) (x-1 ) ( x + 3 ) ; l) (4x + 1 ) (4x - 5) ; Va rog frumos. Multumesc

1

Răspunsuri

Cel mai inteligent răspuns!
2014-11-11T18:55:34+02:00
A)  x^{2} : x^{2} = x^{2-2} = x^{0} =1

b)3 x^{2} :x=3 x^{2-1} =3x

c)-12 x^{2} y:(2x)= \frac{12 x^{2} y}{2x} =6xy

d) x^{2} : x^{3} = x^{2-3} = x^{-1} = \frac{1}{x}

e)3x*(-4x)=-12 x^{2}

f) a^{2} : a^{2} =a ^{2-2} = a^{0} =1

g)2x+6+3x-8=5x-2

h)(x+4)-(x+4)=x+4-x-4=0

i)-(4x+7)+(4x+7)=-4x-7+4x+7=0

j)(x-1)(x-2)= x^{2} -2x-x+2= x^{2} -3x+2

k)(x-1)(x+3)= x^{2} +3x-x-3= x^{2} +2x-3

l)(4x+1)(4x-5)=16 x^{2} -20x+4x-5=16 x^{2} -16x-5